The pioneer transcription factor Zelda controls the exit from regeneration and restoration of patterning in Drosophila. - Bose, A.; Schuster, K.; Kodali, C.; Sonam, S.; Smith-Bolton, R.K. (Science advances, 2025)
Many animals can regenerate tissues after injury. While the initiation of regeneration has been studied extensively, how the damage response ends and normal gene expression returns is unclear. We found that in Drosophila wing imaginal discs, the pioneer transcription factor Zelda controls the exit from regeneration and return to normal gene expression. Optogenetic inactivation of Zelda during regeneration disrupted patterning, induced cell fate errors, and caused morphological defects yet had no effect on normal wing development. Using Cleavage Under Targets & Release Using Nuclease, we identified targets of Zelda important for the end of regeneration, including genes that control wing margin and vein specification, compartment identity, and cell adhesion. We also found that GAGA factor and Fork head similarly coordinate patterning after regeneration and that chromatin regions bound by Zelda increase in accessibility during regeneration. Thus, Zelda orchestrates the transition from regeneration to normal gene expression, highlighting a fundamental difference between developmental and regeneration patterning in the wing disc.